Emergency extracorporeal life support and ongoing resuscitation: a retrospective comparison for refractory out-of-hospital cardiac arrest. Issue 5 (17th February 2017) - Schober, A; Sterz, F; Herkner, H; Wallmueller, C; Weiser, C; Hubner, P; Testori, C
Abstract : Background: In refractory cardiac arrest, with cardiopulmonary resuscitation (CPR) for more than 30 min, chances of survival are small. Extracorporeal cardiopulmonary resuscitation (ECPR) is an option for certain patients with cardiac arrest. The aim of this study was to evaluate characteristics of patients selected for ECPR. Methods: Anonymised data of adult patients suffering refractory cardiac arrest, transported with ongoing CPR to an ED of a tertiary care centre between 2002 and 2012 were analysed. Outcome measure was the selection for ECPR. Secondary outcome was 180 days survival in good neurological condition. Results: Overall, 239 patients fulfilled the inclusion criteria. ECPR was initiated in seven patients. Patients treated with ECPR were younger (46 vs 60 years; p=0.04), had shorter intervals before CPR was started (0 vs 1 min; p=0.013), faster admissions at the ED (38 vs 56 min; p=0.31) and lower blood glucose levels on admission (14 vs 21 mmol/L; p=0.018). Survival to discharge in good neurological condition was achieved in 14 (6%) of all patients. One patient in the ECPR group survived in excellent neurological condition. Age was independently associated with the selection for ECPR (OR 0.07; 95% CI 0.01 to 0.85; p=0.037). Conclusions: Emergency extracorporeal life support was used for a highly selected group of patients in refractory cardiac arrest. Several parameters were associated with the decision, but only age was independently associated with the selection for ECPR. The patient selection resulting in a survival of one patient out of seven treated seems reasonable. Randomised controlled trials evaluating the age limit as selection criteria are urgently needed to confirm these findings.